ANALISIS ANALISIS VEGETASI GULMA PADA LAHAN GAMBUT PERKEBUNAN KELAPA SAWIT (Elaeis queneensis Jacq) DI KELURAHAN TEBING TINGGI OKURA, KECAMATAN RUMBAI PESISIR, PROVINSI RIAU - Ollyvia Rahmadani Pertiwi; Nofripa Herlina; Elsie Elsie (BIO-SITE |Biologi dan Sains Terapan, 2018)
This study aims to determine the types of weed vegetation in oil palm plantations (Elaeis guineensis Jacq) in Tebing Tinggi Okura, Rumbai Pesisir Sub-District, Riau. The research procedure starts from the field survey, the determination of the station is done by purposive random sampling method and is determined by three research stations namely Station I (3-5 years), Station II (5-7 years), Station III (> 7 years). Data is analyzed base on density, frequency, important value index, species diversity index (H '), dominance index, evenness index, uniformity index or similarity. The results were obtained nine types of weeds that are Asystasia gangetica weeds, Calopogonium mucunoides Desv., Davallia denticulata, Dianella ensifolia L., Elaphoglossum blumeanum, Eupatorium inulifolium Kunt, Imperata cylindrica Raeusch, Nephrolepis bisserata Schott., and Wrightia javanica.